Development and Experimental Investigations into Multi-Jet Rotary Nanofinishing Process - Choudhary, Shubham (My University, 2023)
Metallic dies and moulds play a crucial role in manufacturing industries, particularly in industries that produce a large number of identical parts or products. Metallic dies and moulds in manufacturing industries are designed to produce high-precision parts and products that are consistent in quality and dimension. This is especially important in industries where even small deviations in dimensions or specifications can cause product failure or other issues. Increased efficiency using metallic dies and moulds in manufacturing can help to increase efficiency and productivity. The use of automated systems and machines that are designed to work with dies and moulds can speed up the production process and reduce the need for manual labor. The use of metallic dies and moulds can be cost-effective for manufacturing industries in the long run. While the initial investment in the tooling can be high, the cost per part or product can be significantly reduced as a result of the increased efficiency and precision. Most of the automated techniques used for surface polishing of open dies and moulds are still the slowest one with the polishing time in certain cases constitute the significant percentage of overall die manufacturing time. The advances in die polishing technologies have helped to minimize these problems to certain extent and have enabled achievement of better surface finishing. But these processes still have scope for improvements to make them more efficient in the present context of demand for higher manufacturing productivity and the stringent requirement of product quality. Many researchers have proposed various non-conventional post processing techniques such as chemical polishing (CP) and electropolishing (EP), to improve the surface quality. Some have even used integrated techniques combining with electrical polishing (EP), mechanical polishing (MP) and ultrasonic methods, or use of abrasive jet polishing (AJP) and magnetorheological finishing process (MRF) to improve the surface quality. Compared with these non-conventional polishing processes, FJP process is better suited for polishing of dies and moulds, because of better material removal rate, ability to generate small tool influence function (TIF), no heat generation during polishing and better tool life. The fluid jet polishing (FJP) is an ultra-precision and non-contact type polishing process for generating high quality surface finish in metallics dies and moulds manufactured from ductile materials like Monel-400 and AISI H13 die steel. This work presents a study on FJP polishing of Monel-400 and AISI H13 die steel material using a custom designed 3D printed nozzle and Silicon Carbide (SiC) abrasive slurry. The study presents a simultaneous effect of pressure, stand-off distance, polishing time, feed rate and spindle rotation on the surface finish using water based abrasive slurry mixed with water soluble cutting oil. The Central Composite Design (CCD) method was used to develop the experimental plan. ANOVA analysis was performed to develop a regression model and find the contribution of each parameter on the percentage change in surface roughness. The study presents an effect of pressure, stand-off distance and polishing time on Monel- 400 workpiece material. The validation of the developed regression equation was done by polishing the plate of Monel-400 using the optimized parameters: pressure of 9.6𝑏𝑎𝑟, standoff distance of 32.2𝑚𝑚 and polishing time of 170𝑠𝑒𝑐. The optimized FJP parameters successfully generated the surface roughness of 90𝑛𝑚 in one of the experimental tests. The predicted results were in close agreement with the experimental results. Further improving the polishing efficiency, the optimal feed rate of 20𝑚𝑚/𝑚𝑖𝑛 was used to polish 40𝑚𝑚 × 50𝑚𝑚 Monel-400 plate, the surface roughness was reduced from 300𝑛𝑚 to 80𝑛𝑚 in 10 multiple passes showing the reduction in peaks and valleys with surface improvement of 73.33 %. The result shows that the FJP process also tends to improve the life span of Monel- 400 die steel workpieces. The study also presents an effect of pressure, stand-off distance and polishing time on AISI H13 die steel workpiece material. The regression model developed for the FJP process was validated by polishing the plate specimen of AISI H13 having 500𝑛𝑚 average initial surface roughness with the optimized parameters; pressure of 11.1𝑏𝑎𝑟, stand-off distance of 32𝑚𝑚 and polishing time of 174.6𝑠𝑒𝑐. The optimized FJP parameters were able to generate the surface roughness of 240𝑛𝑚 in one of the confirmation tests. In addition, the optimal feed rate of 20𝑚𝑚/𝑚𝑖𝑛 was used to polish 30𝑚𝑚 × 30𝑚𝑚 steel plate made of AISI H13, the surface roughness was reduced from 500𝑛𝑚 to 130𝑛𝑚 in 99.2𝑚𝑖𝑛 showing the reduction in peaks and valleys with surface improvement of 74% which results in enhanced polishing efficiency. Further, the work was extended to presents a simultaneous effect of feed rate and spindle rotation on AISI H13 workpiece material. The regression model developed for the FJP process was validated by polishing the AISI H13 workpiece with 390𝑛𝑚 average initial surface roughness with the optimized process parameters; feed rate of 20𝑚𝑚/𝑚𝑖𝑛 and spindle rotation of 60𝑟𝑝𝑚. The optimized FJP parameters were able to generate the surface roughness of 240𝑛𝑚. To further enhance the polishing efficiency, the optimum process parameters were used to polish AISI H13 die steel workpiece, the surface roughness was reduced from 390𝑛𝑚 to 110𝑛𝑚 in 15𝑚𝑖𝑛 with 12 number of passes which shows the reduction in peaks and valleys with surface improvement of 71.79%.
PhD Thesis
Keywords: Fluid jet-polishing; CCD; ANOVA; 3D printed Ti64; SiC abrasive; Surface roughness